Inovasi PT Pos Indonesia Dalam Mempertahankan Dan Menjaga Eksistensinya - Yus Ramadhani; Nur Ahmadi Bi Rahmani (ManBiz: Journal of Management and Business, 2022)
The existence of PT POS Indonesia is currently experiencing a lot of decline, this fact is a response to technological sophistication. In the past, PT POS Indonesia was one of the institutions in charge of correspondence and sending letters between regions. Until now, this phenomenon has been replaced by technology such as the emergence of mail to short messages in several smartphone applications. Therefore, Indonesian POS service providers must have an innovation strategy in order to attract the hearts of their customers. This innovation is one of the challenges that must be lived and sought by PT POS Indonesia. One of the branches of PT POS Indonesia Persero is in Pematang Siantar. The purpose of this study is to find out some of the innovations implemented by PT POS Indonesia (Persero) in Pematang Siantar to maintain its existence amidst the dynamics of technological sophistication. The research method used in this study is a qualitative type with a descriptive approach. The results showed that PT POS Indonesia (Persero) Pematang Siantar made changes to the management and leadership system in the internal area to reach a wider market while in its service to the community PT POS Indonesia had facilitated with a pick-up service to the house so that mobility carried out by the community was easier. Keywords: PT POS Indonesia (Persero), Pematang Siantar, Innovation, Service